2020
DOI: 10.1007/s40858-020-00354-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage quantification in Physalis peruviana L. infected by the new putative sobemovirus physalis rugose mosaic virus

Abstract: A putative new virus, physalis rugose mosaic virus (PhyRMV), has been reported more frequently in Physalis peruviana associated with severe symptoms. In this study the damage caused by sap-inoculated PhyRMV in P. peruviana was assessed based on the comparison of host vegetative and reproductive parameters between virus-infected and healthy plants. Infected plants confirmed using molecular assays, showed a reduction in growth, leaf area, specific leaf area (SLA) and relative chlorophyll content. PhyRMV-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
3
0
0
Order By: Relevance
“…Double infection prevented the development and production of Physalis plants, making physalis crops unfeasible. This result corroborates that of Gorayeb et al (2020), who reported that PhyRMV‐infected P . peruviana plants produced 70% fewer fruits, which were of lower quality, than healthy plants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Double infection prevented the development and production of Physalis plants, making physalis crops unfeasible. This result corroborates that of Gorayeb et al (2020), who reported that PhyRMV‐infected P . peruviana plants produced 70% fewer fruits, which were of lower quality, than healthy plants.…”
Section: Discussionsupporting
confidence: 92%
“…TA B L E 4 Physicochemical analysis of fruits from Physalis peruviana plants infected with physalis rugose mosaic virus (PhyRMV) or groundnut ringspot virus (GRSV) and the healthy (control) plants. The results of the present study clearly show that infection of This result corroborates that of Gorayeb et al (2020), who reported that PhyRMV-infected P. peruviana plants produced 70% fewer fruits, which were of lower quality, than healthy plants. GRSV also causes significant damage, especially to varieties of other species that do not contain the tospovirus resistance gene.…”
Section: Ta B L Esupporting
confidence: 92%
See 1 more Smart Citation